2018
DOI: 10.3390/molecules23071581
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II) Complexes of 4-[(1E)-N-{2-[(Z)-Benzylidene-amino]ethyl}ethanimidoyl]benzene-1,3-diol Schiff Base: Synthesis, Spectroscopic, In-Vitro Antioxidant, Antifungal and Antibacterial Studies

Abstract: The current study reports the synthesis of copper complexes of a tridentate Schiff base ligand. The compounds of the type [Cu(L)X]∙n(H2O) (where L = tridentate ONN Schiff base ligand, X = Cl−, Br−, SCN−, NO3−, CH3COO−), were characterized on the basis of elemental analyses, FT-IR, UV-vis, molar conductance, 1H-NMR, XRD and thermal analyses. The spectra revealed that the Schiff base ligand acts as a tridentate ligand through two azomethine nitrogen atoms and a phenolic oxygen atom. The molar conductance measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…The results demonstrate a formula of either 2 mol of bidentate hydrazone Schiff base ligands coordinate to 1 mol of copper(II) ion involving L 1 and L 2 , while 3 mol of L 3 Schiff base ligands coordinate to 1 mol of copper(II) 1 3,531 1,675 1,494 L 2 3,243 1,651 1,491 L 2 3,528 1,675 1,493 L 3 3,341 1,670 1,445 L 3 3,508 1,677 1,494 ion; as shown in Table 2. The proposed structures of Schiff base metal complexes are shown in Figure 3 and found to be comparable with some previously reported complexes involving copper(II) ion and hydrazones [30,31,32]. We predict that the metal complexes were obtained from the chelation of the ligands through the N and O atoms, forming stable five-membered chelate ring along with deprotonation of amine hydrogen atoms.…”
Section: General Features and Computational Studies Of Schiff Base-cosupporting
confidence: 84%
See 1 more Smart Citation
“…The results demonstrate a formula of either 2 mol of bidentate hydrazone Schiff base ligands coordinate to 1 mol of copper(II) ion involving L 1 and L 2 , while 3 mol of L 3 Schiff base ligands coordinate to 1 mol of copper(II) 1 3,531 1,675 1,494 L 2 3,243 1,651 1,491 L 2 3,528 1,675 1,493 L 3 3,341 1,670 1,445 L 3 3,508 1,677 1,494 ion; as shown in Table 2. The proposed structures of Schiff base metal complexes are shown in Figure 3 and found to be comparable with some previously reported complexes involving copper(II) ion and hydrazones [30,31,32]. We predict that the metal complexes were obtained from the chelation of the ligands through the N and O atoms, forming stable five-membered chelate ring along with deprotonation of amine hydrogen atoms.…”
Section: General Features and Computational Studies Of Schiff Base-cosupporting
confidence: 84%
“…This is presumably due to the intramolecular hydrogen bonding within the molecule. The appearance of new bands in the low-frequency infrared region (< 1, 000 cm −1 ) between 520 cm −1 and 557 cm −1 is attributed to υ Cu−N ; while the bands within the region of 483-625 cm −1 are assigned to υ Cu−O [30,33]. These pieces of evidence confirmed that the ligands are coordinated to the copper(II) ion via the imine nitrogen atom and carbonyl oxygen atom albeit this region has been more difficult to assess.…”
Section: General Features and Computational Studies Of Schiff Base-comentioning
confidence: 95%
“…However, the efficient activity againstABTS •+ and weak anti-DPPH radical activity is evocative of a substitute scavenging mechanism of the methanol extract of P. graveolens. This is further supported by the fact that most scavenging processes are accomplished either by electron or proton donation to unstable radical, as reported by various studies 18,20 .…”
Section: Antioxidant Effect Of the Optimized P Graveolens Extractsupporting
confidence: 59%
“…Minimum inhibitory concentrations (MIC) of extracts for antibacterial activity were determined using the micro dilution bioassay as described [19][20] . Overnight cultures (incubated at 37°C in a water bath with an orbital shaker) of two Gram-positive (Staphylococcus aureus and Enterococcus faecalis) and two Gram-negative (Escherichia coli and Salmonella typhi) bacterial strains were diluted with sterile Mueller-Hinton (MH) broth to give final inoculums of approximately 10 6 CFU/ml (colony forming units).…”
Section: Micro-dilution Assay For Bacteriamentioning
confidence: 99%
See 1 more Smart Citation